Pancreatic abnormalities and AIDS related sclerosing cholangitis. Issue 4 (August 1997) - Teare, J P; Daly, C A; Rodgers, C; Padley, S P; Coker, R J; Main, J; Harris, J R; Scullion, D; Bray, G P; Summerfield, J A
Abstract : OBJECTIVES: Biliary tract abnormalities are well recognised in AIDS, most frequently related to opportunistic infection with Cryptosporidium, Microsporidium, and cytomegalovirus. We noted a high frequency of pancreatic abnormalities associated with biliary tract disease. To define these further we reviewed the clinical and radiological features in these patients. METHODS: Notes and radiographs were available from two centres for 83 HIV positive patients who had undergone endoscopic retrograde cholangiopancreatography for the investigation of cholestatic liver function tests or abdominal pain. RESULTS: 56 patients had AIDS related sclerosing cholangitis (ARSC); 86% of these patients had epigastric or right upper quadrant pain and 52% had hepatomegaly. Of the patients with ARSC, 10 had papillary stenosis alone, 11 had intra- and extrahepatic sclerosing cholangitis alone, and 35 had a combination of the two. Ampullary biopsies performed in 24 patients confirmed an opportunistic infection in 16. In 15 patients, intraluminal polyps were noted on the cholangiogram. Pancreatograms were available in 34 of the 45 patients with papillary stenosis, in which 29 (81%) had associated pancreatic duct dilatation, often with associated features of chronic pancreatitis. In the remaining 27 patients, final diagnoses included drug induced liver disease, acalculous cholecystitis, gall bladder empyema, chronic B virus hepatitis, and alcoholic liver disease. CONCLUSION: Pancreatic abnormalities are commonly seen with ARSC and may be responsible for some of the pain not relieved by biliary sphincterotomy. The most frequent radiographic biliary abnormality is papillary stenosis combined with ductal sclerosis.